Transnational Film as Linguistic and Artistic Practice: Educational Perspectives on Global–Local Collaboration - Leonhard Fischer (Britain International for Academic Research (BIAR) Publisher, 2009)
The globalization of the film industry has fostered increased transnational collaboration, transforming not only production practices but also linguistic expression, artistic creativity, and educational value within contemporary cinema. Focusing on partnerships between regional film industries and major global centers, this study examines how multilingual communication, cultural narratives, and artistic practices are negotiated in transnational contexts. Drawing on the theoretical framework of Diffusion of Innovation, the analysis highlights how linguistic choices, including code-switching, translation, and subtitling, function as key elements in mediating cultural meaning and audience accessibility. At the same time, film is approached as an educational medium that facilitates intercultural learning, identity formation, and creative engagement. The findings reveal that transnational film collaborations generate hybrid forms of artistic and linguistic expression, blending local cultural elements with global cinematic conventions. While these collaborations provide opportunities for knowledge exchange, skill development, and expanded audience reach, they also reflect underlying power asymmetries that influence language dominance, narrative framing, and cultural representation. From an educational perspective, transnational cinema serves as a valuable resource for developing linguistic awareness, critical thinking, and intercultural competence among learners. The study emphasizes the need to integrate film-based approaches into language and arts education, encouraging students to critically engage with global media while preserving local cultural identities. In conclusion, global–local dynamics in film collaboration highlight the complex interplay between language, art, and education in shaping contemporary media practices. These collaborations function both as spaces of creative innovation and as sites of negotiation where linguistic diversity and cultural meaning are continuously redefined.